Определение магнитных индукций в магнитопроводах силовых трансформаторов при совместном использовании анизотропной и изотропной электротехнических сталей - Пентегов, И.В.; Рымар, С.В.; Levin, M.I.; Lavreniuk, A.V. (Електротехніка і електромеханіка, 2015)
Разработана методика расчета значений магнитных индукций в частях шихтованных магнитопроводов силовых
трансформаторов при совместном использовании разных типов электротехнических сталей, в частности – анизотропной и изотропной, позволяющая в дальнейшем рассчитывать потери в магнитопроводах трансформаторов
(потери холостого хода) и ток холостого хода. Розроблено методику розрахунку значень магнітних індукцій у частинах шихтованих магнітопроводів силових трансформаторів при спільному використанні різних типів електротехнічних сталей, зокрема – анізотропної й ізотропної, що дозволяє надалі розраховувати втрати в магнітопроводах трансформаторів (втрати холостого ходу) і струм
холостого ходу. Purpose. The development of calculation method to determinate
the flux densities in different parts of the magnetic cores of distribution transformers, what built from different types magnetic steel
(mixed core). Methodology. The method is based on the scientific
positions of Theoretical Electrical Engineering – the theory of the
electromagnetic field in nonlinear mediums to determine the distribution of magnetic flux in mixed core of transformer, what are
using different types of steel what have the different magnetic
properties. Results. The developed method gives possible to make
calculation of the flux density and influence of skin effect in different parts of the magnetic cores of distribution transformer, where
are used mix of grain oriented (GO) and non grain oriented
(NGO) steels. Was determinate the general basic conditions for
the calculation of flux density in the laminations from grain and
non grain oriented steels of the magnetic core: the strength of
magnetic field for the laminations of particular part of mixed core
is the same; the sum of the magnetic fluxes in GO and NGO steels
in particular part of mixed core is equal with the designed magnetic flux in this part of mixed core. Discover, the magnetic flux in
mixed core of the transformer has specific distribution between
magnetic steels. The flux density is higher in laminations from GO
steel and smaller in laminations from the NGO steel. That is happened because for magnetic flux is easier pass through laminations from GO steel, what has better magnetic conductance than
laminations from NGO steel. Originality. The common using of
different types of magnetic steels in cores for distribution transformers gives possibility to make design of transformer with low
level of no load losses, high efficiency and with optimal cost.
Practical value. The determination of the flux density in different
parts of magnetic core with GO and NGO steels gives possibility
make accurate calculation of no load losses and magnetizing
current of the transformer.